Tracking geomorphic recovery in process‐based river management. (22nd May 2018) - Fryirs, Kirstie A.; Brierley, Gary J.; Hancock, Fergus; Cohen, Tim J.; Brooks, Andrew P.; Reinfelds, Ivars; Cook, Nick; Raine, Allan
Abstract: Human disturbance induces significant geomorphic changes to river systems. In eastern Australia, land‐use practices such as clearance of forests and riparian vegetation, and removal of wood from channels in the 19th and 20th centuries induced widespread geomorphic impacts. However, since the 1970s, there has been a noticeable shift in the geomorphic condition of many rivers in eastern New South Wales (NSW). This transition to a recovery trajectory reflects a reduction in land‐use pressures and improved farming practices on the one hand and adoption of recovery enhancement approaches to river conservation and rehabilitation by management authorities on the other. Monitoring and tracking changes in condition by state government agencies involves identifying when geomorphic recovery is occurring so that decision‐support frameworks can determine whether river management is required, where, when, and how much to intervene to enhance river recovery and when to opt‐out of management because the system requires little (or no) intervention. Here, we document procedures that are used to manage process‐based, recovery enhancement in NSW. Following a brief review of river change in eastern NSW since European settlement, we outline an approach to identify and measure key geomorphic indicators of river recovery for different river types. We use case studies to demonstrate examples of geomorphic river recovery, prior to showing how state government agencies in NSW are monitoring trajectories and rates of recovery. Broader implications of this 'good news story' are discussed.